2021
DOI: 10.1007/s41748-021-00284-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effectiveness of Catch Crops as a Nature-Based Solution to Mitigate Surface Soil and Water Losses as an Environmental Regional Concern

Abstract: The main goal of this research was to conduct a biophysical, economic, social, and perception-based approach to foresee the solutions that could be used to mitigate the soil loss problem cost-effectively in “La Ribera del Xúquer” district (Valencia Region, Spain). To achieve these goals, a farmer perception survey was carried out, and an assessment of the biophysical impact of catch crops on soil organic matter, bulk density, steady-state infiltration rate (double-ring infiltrometer) and runoff generation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The GSLDI enters the category of GIS tools based on artificial intelligence employed to solve complex issues. Therefore, it suits the analysis of land degradation processes such as soil erosion that integrates numerous factors 123 , 124 . When compared to similar models focused on land degradation, the GSLDI integrates a pastoral activity (i.e., small ruminants grazing) that is the most common farming practice in certain parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The GSLDI enters the category of GIS tools based on artificial intelligence employed to solve complex issues. Therefore, it suits the analysis of land degradation processes such as soil erosion that integrates numerous factors 123 , 124 . When compared to similar models focused on land degradation, the GSLDI integrates a pastoral activity (i.e., small ruminants grazing) that is the most common farming practice in certain parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a slight increase in the agricultural lands appeared in 2012 and 2018 (2.5% and 3.1% respectively in the mentioned sub-basins). Recent studies conducted in E and SE Spain (Alonso-Sarría et al, 2016;Cerdà et al, 2021a andCerdà et al, 2021b;García-Ruiz and Lana-Renault, 2011) suggest that these recent changes in land abandonment of agricultural areas respond to climate-related factors, topographical limitations such as the occurrence of small landslides, as well as numerous socio-economic factors derived from the reduction of subsidies by the European Agricultural Policies, among others. We also hypothesize that reduction in precipitation already identified in the region (Valdes-Abellan et al, 2017) jointly with the controversy about the use of external water resources from other basins (Molina- Giménez and Melgarejo-Moreno, 2015;Sánchez-Galiano et al, 2017;Melgarejo-Moreno et al, 2019;Ricart and Rico, 2019) could be other two additional factors that are reducing the profits of rain-fed agriculture and increasing the risk of irrigated practices promoting the abandonment of the agriculture in this region.…”
Section: Land-use Changes and Curve Number Variationsmentioning
confidence: 99%
“…Over the world, and especially across the Mediterranean belt, several authors have reported that river basin systems are being affected by high human pressures and immediate solutions are needed (Gassman et al, 2007;García and Cutillas, 2014;Cerdà et al, 2021a andCerdà et al, 2021b). Deforestation, land fragmentation, wetland cultivation or rapid urbanization are some examples of water catchment degradation, resulting in reduced baseflow, drying up of small streams and water wells, floods and water shortages (Andrade and Szlafsztein, 2018;Alonso-Sarría et al, 2016;Gao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of rapid and non‐planned changes in LUCC can manifest as land degradation, biodiversity loss, climate change, species invasion, and decreased ecosystem service functioning in a given region (Shi et al, 2022; Foley et al, 2005; Hesslerova et al, 2012; Jarvie et al, 2008; Jiang, 2013; Piao et al, 2007; Pielke, 2005). Land transformation from original ecosystem status to agricultural, industrial or urbanized uses can have critical consequences (Ceccarelli et al, 2014; Cerdà et al, 2021; Rodrigo‐Comino et al, 2021). Recent investigations suggest that karst ecosystems are extremely fragile, once degradation happens, they are unlikely to recover in the short term (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%